Psychometric properties of the Chinese version of the attitude towards the prevention of incontinence-associated dermatitis (C-APrIAD) among Chinese nurses. Issue 3 (August 2021) - Zhang, Qi; Zhang, Ke; Wang, Yuxin; Jia, Yibo; Gu, Jiaxin; Li, Xintong; Li, Mingzi
Abstract: Aim: Nurses' attitude is a significant determinant of incontinence-associated dermatitis (IAD) prevention, and a positive attitude may benefit quality improvement projects. This research aimed to translate the attitude towards the prevention of incontinence-associated dermatitis instrument (C-APrIAD) into Chinese and test the reliability and validity among Chinese nurses. Methods: The C-APrIAD was translated into Chinese using a standard procedure of backward-forward translation and cross-cultural adaption. Totally 170 nurses were recruited through the convenience sampling method from three tertiary hospitals in Tianjin, Shandong, and Heilongjiang province of China. Reliability (internal consistency, stability) and validity (content validity, structure validity, and convergent validity), were assessed. Convergent Validity was evaluated by correlation with the General Self-Efficacy Scale (GSES). Results: Of the 170 completed questionnaires, 158 (93%) were suitable for analysis. The item-total correlation coefficients ranged from 0.39 to 0.80. The content validity of C-APrIAD was 0.96. A factor analysis indicated the construct of a 14-item instrument in a four factors solution: (1) beliefs about the impact of IAD on patients, (2) beliefs about team responsibility to prevent IAD, (3) beliefs about personal responsibility to prevent IAD, and (4) beliefs about the effectiveness of IAD prevention products and procedures. The correlation coefficient between the GSES and C-APrIAD was 0.49 ( P  < 0.01). For the total instrument, the Cronbach's α coefficient was 0.87 and the test-retest reliability was 0.99. Conclusion: The C-APrIAD is reliable and valid. The C-APrIAD may benefit nursing research as well as clinical practice to optimize interventions to improve IAD prevention. Highlights: · It is necessary to accurately assess nurses' attitude towards the prevention of incontinence-associated dermatitis (IAD) in China. · This paper provides a valid and reliable measure for evaluation nurses' attitude towards the prevention of IAD in China. · It can be used in various studies to measure nurses' attitude towards the prevention of IAD in China, and allowing inter-cultural or international comparisons.